2001
DOI: 10.1289/ehp.01109943
|View full text |Cite
|
Sign up to set email alerts
|

Diethylnitrosamine causes pituitary damage, disturbs hormone levels, and reduces sexual dimorphism of certain liver functions in the rat.

Abstract: The acute toxicity of diethylnitrosamine (DEN) to the liver has been well documented in the literature, but whether DEN also affects the endocrine parameters has been addressed in only a few studies. We thus investigated the effects of DEN on pituitary, serum hormone levels, and certain sex-differentiated liver enzymes in this study. Adult male Wister rats were intraperitoneally injected with DEN at a single dose of 200 mg/kg and were sacrificed at 1, 3, 7, and 35 days after injection; DEN-treated females were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…In the present investigation, DEN induced hepatocellular damage is clearly evidenced by the marked elevation in the activity of serum AST, ALT and ALP which is in agreement with other researches (4,5,(14)(15)(16). These enzymes are the most sensitive markers employed in the diagnosis of hepatic damage because they are cytoplasmic in location and are released into the circulation after cellular damage (3,17). Current study demonstrated that treatment with EPE for 30 days reduced different parameters in EPE + DEN group and these decreases were significant in AST, BUN and total and direct bilirubin (P < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…In the present investigation, DEN induced hepatocellular damage is clearly evidenced by the marked elevation in the activity of serum AST, ALT and ALP which is in agreement with other researches (4,5,(14)(15)(16). These enzymes are the most sensitive markers employed in the diagnosis of hepatic damage because they are cytoplasmic in location and are released into the circulation after cellular damage (3,17). Current study demonstrated that treatment with EPE for 30 days reduced different parameters in EPE + DEN group and these decreases were significant in AST, BUN and total and direct bilirubin (P < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…In the present investigation, DEN induced hepatocellular damage is clearly evidenced by the marked elevation in the activity of serum AST, ALT and ALP which is in agreement with other researches (4, 5, 14-16). These enzymes are the most sensitive markers employed in the diagnosis of hepatic damage because they are cytoplasmic in location and are released into the circulation after cellular damage (3, 17). Current study demonstrated that treatment with EPE for 30 days reduced different parameters in EPE + DEN group and these decreases were significant in AST, BUN and total and direct bilirubin ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, diethylnitrosamine has been shown to be hormonally active (Liao et al 2001), as well as phthalates (Hoppin et al 2002). There is evidence from animal data that phthalates have adverse reproductive eVects in males (Foeter et al 2001;Gray et al 2000;Mylchreest et al 2002;Nagao et al 2000), and possibly also females (Ema and Miyawaki 2001).…”
Section: M¡p+mentioning
confidence: 99%